Effect of DEHP on SCFA Production by Anaerobic Fermentation of Waste Activated Sludge. (28th February 2020) - Gong, Rui; Tang, Xiang; Fan, Changzheng; Zhang, Baowei; Zhou, Man
Abstract : Diethylhexyl phthalate (DEHP) is a common plasticizer in industrial production. Recently, environmental problems caused by microplastics have drawn wide attention. As the microplastics have a large specific surface area, the release rate of the plasticizer from the microplastics to the environment is accelerated. The DEHP in the wastewater enters the wastewater treatment plants (WWTPs) along with the urban pipeline. After DEHP enters the WWTPs, it may affect the anaerobic fermentation with waste activated sludge (WAS) as raw material. So far, there has been no study on the effect of DEHP on anaerobic fermentation of WAS. Our study focused on the impact of exogenous DEHP on WAS anaerobic fermentation, and the results showed that DEHP mainly affects the solubilization stage of sludge anaerobic digestion, but has no significant effect on other stages. It does not affect the total yield and composition of short-chain fatty acids (SCFA). However, DEHP inhibited the solubilization process of WAS anaerobic fermentation, which was mainly manifested by the changes of soluble protein and soluble polysaccharide in the system. The results of the analysis of microbial communities revealed that the addition of DEHP did not change the diversity of microbial communities, but caused a change in the abundance of microbial organisms. DEHP reduced the abundance of acetogen bacteria and increased the abundance of methanogens. This work provides some insights into WAS fermentation systems in the presence of DEHP and helps to gain a better understanding of the potential environmental hazards of microplastics.